Getting back into work after job loss: The role of partner effects - Mark L. Bryan; Simonetta Longhi (University of Essex, Institute for Social and Economic Research (ISER), 2015)
We investigate the reaction of couples to a job loss during periods of growth and recession in the UK focussing on re-employment of the spouse who lost their job. Re-employment was faster for those with a partner in work, but was not generally affected by other measures of the partner's labour market attachment or resources. For men, the strongest partner effects were for entry into high quality jobs; and having a working partner substantially mitigated the negative impact of the recession on entry into these jobs. For women, an employed partner was associated with a greater likelihood of re-entry into any type of job. Hence, while dual earner families may be able to restore the pre-job loss income level, single earner families are more likely to be trapped in cycles of low-quality jobs and no jobs leading to a decrease in household income over time. The difference in outcomes between single and dual earner couples is likely to increase during recessions.
Keywords: J22; J64; 330; added-worker effect; recession; employment; household labour supply